Ultraviolet radiation affects intumescence development in ornamental sweetpotato (Ipomoea batatas) - Craver, Joshua K.; Miller, Chad T.; Williams, Kimberly A.; Bello, Nora M. (My University, 2015)
Intumescences are a physiological disorder characterized by hypertrophy and possibly hyperplasia of plant tissue cells. Ultimately, this disorder results in the death of the affected cells. Previous observations and research suggest that the quality and quantity of light to which plants are exposed may be a factor in development of the disorder. The purpose of this study was to assess the preventive effect of ultraviolet-B (UVB) radiation on intumescence development in ornamental sweetpotato (Ipomoea batatas). Two sweetpotato cultivars, Sidekick Black and Ace of Spades, were grown under light treatments consisting of 1) normal greenhouse production conditions; 2) supplemental UVB lighting; 3) supplemental UVB lighting with Mylar® sleeves over the lamps to block UVB radiation; and 4) control lighting with full spectrum lamps. Treatments were administered for 2 weeks, and the experiment was repeated twice. ‘Ace of Spades’ was highly susceptible to intumescence development, whereas ‘Sidekick Black’ was much less susceptible to the disorder. For ‘Ace of Spades’, the addition of UVB radiation significantly reduced the number of leaves affected with intumescences when compared with plants grown under the other light treatments; this UVB effect was not apparent for ‘Sidekick Black’. Furthermore, there was no evidence for reduced plant growth under UVB light in either cultivar, but side effects from the radiation included leaf discoloration and deformities. This study indicates a cultivar-specific effect of UVB light in preventing intumescence development on ornamental sweetpotato, therefore suggesting a potential genetic component in intumescence susceptibility. These results provide further insight in better understanding intumescence development and how to prevent the disorder.
Keywords: Floriculture; Greenhouse management; UVB light; Controlled environment; Oedema